Characterization of the optical gain at 1550 nm of erbium-oxalate single crystals - López-Romero, R. E.; Pérez-Sánchez, G. G.; Aldaya, I. [UNESP]; Medina, D. Y.; Martínez-Piñeiro, E. L.; Figueroa, I. A.; Escudero, R. (Optica Publishing Group, 2024)
Erbium is well-recognized as a key element for optical amplification at the 1550 nm operation band. However, the limited solubility of this material in vitreous matrices sets a critical constraint to the achievable optical gain, which limits its applicability in photonic integrated platforms. One of the solutions to increase the concentration of erbium is to employ a crystalline structure instead of a glass. In this paper, we characterize samples of erbium and erbium-ytterbium oxalate single crystals synthesized using the gel diffusion method. X-ray diffraction spectra and thermogravimetric analyses reveal that the synthesis method indeed generated the expected compound, and the pump-and-probe experiments demonstrate an on-off gain coefficient of ≈ 6.5 dB/mm, making this material a high-potential candidate for the implementation of integrated optical amplifiers.